Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Mutiara Hexagon Balaraja Banten - Jessika Putri; Bonar Frans Sihite (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this research is to determine the influence of work motivation and work discipline on employee performance at PT. Mutiara Hexagon Balaraja Banten. The method used is quantitative. The sampling technique used the Slovin formula and the sample obtained in this study was 71 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests. The results of the research are that work motivation has a positive effect on employee performance with a simple linear regression equation Y = 29.443 + 0.358X1, a correlation value of 0.439, meaning that the two variables have a moderate level of relationship. The coefficient of determination value is 19.2%. Hypothesis testing obtained tcount > ttable or (4.055 > 1.995). In this way, Ho1 is rejected and Ha1 is accepted, meaning that there is a positive influence of work motivation on employee performance. Work discipline has a positive effect on employee performance with a simple linear regression equation Y = 22.658 + 1.000X2, a correlation value of 0.615, meaning the two variables have a strong level of relationship. The coefficient of determination value is 43.0%. The hypothesis test obtained is tcount > ttable or (6.479 > 1.995), meaning that Ho2 is rejected and Ha2 is accepted, meaning that there is a positive influence on employee performance. Work motivation and work discipline have a positive effect on employee performance with the multiple linear regression equation Y = 17.322 + 0.200X1 + 0.853X2, a correlation value of 0.656, meaning that work motivation and work discipline have a strong relationship with employee performance. The coefficient of determination value is 43.0% while the remaining 57.0% is influenced by other factors. Hypothesis testing obtained a value of Fcount > Ftable or (25.640 > 3.13). Thus, Ho3 is rejected and Ha3 is accepted. This means that there is a positive influence of work motivation and work discipline on employee performance.